Advanced topics in database research, Volume 5 - SIAU, Keng (Institutional Knowledge at Singapore Management University, 2006)
Advanced Topics in Database Research is a series of books on the fields of database, software engineering, and systems analysis and design. They feature the latest research ideas and topics on how to enhance current database systems, improve information storage, refine existing database models, and develop advanced applications. Advanced Topics in Database Research, Volume 5 presents the latest research ideas and topics on database systems and applications, and provides insights into important developments in the field of database and database management. This book describes the capabilities and features of new technologies and methodologies, and presents state-of-the-art research ideas, with an emphasis on theoretical issues regarding databases and database management. © 2006 by Idea Group Inc. All rights reserved.